BAS/BSCR29 Apolipoprotein(a) impairs adaptive remodelling in human saphenous vein endothelial and smooth muscle cells. Issue 17 (26th August 2010) - Riches, K; Franklin, L; Chowdhury, R; Maqbool, A; O'Regan, D J; Ball, S G; Koschinsky, M L; Turner, N A; Porter, K E
Abstract : Apolipoprotein(a) (apo(a)), a unique glycoprotein component of plasma lipoprotein(a) (Lp(a)), exhibits resistance to classical lipid-lowering treatments. Coronary artery bypass grafting (CABG) is commonly used to bypass coronary arteries diseased by atherosclerosis, routinely using the saphenous vein (SV) as a conduit. Early after grafting the SV adapts to the arterial environment through re-endothelialisation, and increased motility of smooth muscle cells (SMC). A clinical association between Lp(a) and coronary artery disease is evident; however, its role in vein graft failure is less clear. Endothelial cells (EC) and SMC were cultured from the SV of patients undergoing CABG. The influence of apo(a) on cellular activity was examined by proliferation (cell counting), chemotaxis (modified Boyden chamber) and chemokinesis (scratch wound) assays. Apo(a) significantly inhibited SV-EC proliferation (n=9, p<0.001). Although no effect on SV-SMC proliferation was apparent, apo(a) markedly modulated SMC motility and appeared to act as a chemorepellent. When SMC were acutely exposed to a gradient of apo(a), they consistently migrated away from the source (n=6, p<0.01). Chronic exposure to apo(a) in the scratch wound model also revealed that the speed of migration was reduced (n=5, p<0.01). Remodelling of the SV is essential for adaptation to an arterial environment, and key to its function as a successful bypass graft. Our studies show that apo(a) inhibits EC proliferation, potentially compromising endothelial repair in the grafted vein. Furthermore, the chemorepellent effect of apo(a) may also impede critical SMC migration required for effective integration. Lp(a) is therefore likely to contribute to impaired SV adaptation and inferior graft patency.